Classification System for Heart Disease Using Bayesian Classifier - Magendram, Anusha (2007)
Increase of hearth problem in this world is rising each day. Classification system for heart disease is a system that able to justify whether a patient has heart problem or not. This is a new approach that able to use by doctors to rectify the heart problem. This system was developing base on to three main part which is data processing, testing and implementation of the algorithm. In this system a Bayesian algorithm was used in order to implement the system. This system was mainly developing using java programming. Apache Tom cat was used as a server in order to run the application smoothly. This system is tested using the test and training data set. It has proven that the system able to provide an accurate result on justifying whether the patient has has problem or not. As a conclusion by using this system doctors able to improvise the effectiveness in medical field.